Problemy współczesnej gospodarki Ukrainy — analiza struktury PKB - Butyter, Daniel (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
Each sector of Ukraine’s economy needs changes as well as allocation of great financial resources for competitive and proper functioning. Solving the main problems of development of Ukraine’s economy will make this country a major player on the international arena. The sources of highest income in the economy of Ukraine include mining and metallurgy sector, but it is so not due to innovative economy, but due to support from the state, and large private capital investments.
Keywords: Ukraina; PKB; choroba holenderska; produkcja przemysłowa; metale i hutnictwo; górnictwo